Effect of Medicago sativa Addition on Physicochemical, Nutritional and Functional Characteristics of Corn Extrudates - Marta Igual; Maria Simona Chiş; Sonia Ancuța Socaci; Dan Cristian Vodnar; Floricuța Ranga; Javier Martínez-Monzó; Purificación García-Segovia (Foods, 2021)
Currently, extrudates are considered unhealthy products, being characterized as high in calories; rich in fat, sugar, and salt; and low in nutritional compounds. The aim of this study was to assess the influence of lucerne (Medicago sativa) on the physicochemical, nutritional, and functional characteristics of corn extrudates. In order to achieve these goals, water content, water activity, expansion index, bulk density, porosity, hygroscopicity, optical properties, antioxidant activity, individual phenolic acids, folates, individual flavonoids, and volatile compounds were analyzed. The results showed that the typical characteristics of corn extrudates such as expansion, crunchiness, and density were maintained with 10% lucerne addition, highlighting a strong negative Pearson correlation (p < 0.05) between all studied parameters and lucerne addition. On the other hand, the lucerne addition caused a linear increase of bioactive compounds, showing positive Pearson correlations between flavonoids, folates, and antioxidant activity. The volatile profile of corn extrudates improved with the addition of lucerne leading to volatile compounds such as limonene, β-mircene, and hexanal. Overall, considering the textural, nutritional, and functional characteristics of corn extrudates, we determined that a percentage addition on 10% lucerne could be successfully used in the manufacturing of corn extrudates.